Traditional Chinese martial art Wushu to improve the mental state and physical fitness of students: designing space for optimal practice and training - Tu, Zhixing; Zhong, Lei; Xie, Jiahui (Frontiers in Psychology, 2025)
IntroductionTraditional Chinese martial arts (Wushu) possess the potential to enhance both the psychological resilience and physical capacities of learners. Their effective implementation necessitates consideration of spatial and architectural features. This study investigates the impact of spatial-architectural determinants on the psychophysiological adaptation of Wushu practitioners within Chinese and European pedagogical systems.MethodsA mixed-methods approach was employed, combining quantitative biomechanical assessments (n = 184 trainees) with qualitative ethnographic observations (24 training settings over 4-week immersion periods) and semi-structured interviews (n = 42 instructors). Architectural parameters—including ceiling height, floor elasticity, and acoustic properties—were systematically documented, alongside measurements of biomechanical performance indicators.Results and discussionChinese training environments, characterized by high ceilings (>4 m) and specialized wooden flooring, correlated with superior flexibility (hip flexion: 142° ± 3.6° vs. 130° ± 3.8°; p < 0.01) and cardiovascular efficiency (shuttle run: 987 ± 42 m vs. 924 ± 38 m; p < 0.01). European facilities, utilizing rigid synthetic materials, demonstrated advantages in explosive strength metrics (vertical jump: 54.3 ± 3.1 cm vs. 50.0 ± 2.9 cm; p < 0.05). Ceiling height emerged as the dominant architectural predictor of flexibility parameters (β = 0.73, p < 0.001); acoustic characteristics significantly influenced exercise execution speed (β = −0.68, p < 0.001); and spatial volume affected cardiorespiratory adaptation (β = 0.65, p < 0.001). Environments incorporating traditional design elements improved attentional resilience by 27% compared to modernized spaces. The application of data-driven spatial design principles—such as the inclusion of ritualized zones, hierarchical spatial organization, and tailored acoustic environments—represents an underexplored domain within martial arts pedagogy with promising implications for educational practice.